Working for the Common Good: Where Practice Meets Theory - Beech, Lisa (Victoria University of Wellington Law Review, 2013)
The ideal of the common good inspires many people of goodwill to undertake action in their communities and in public debates to improve social wellbeing. In Catholic Social Teaching, working for the common good calls each person to work for the good of each person and of all people. However, in public discussion and debate, the understanding of the common good found in Catholic Social Teaching is often confused with similar sounding but quite different concepts of the greater good, public good and public interest. This article is based on a joint presentation with Bishop Philip Richardson given at the "Recovering the Common Good" Conference. It presents the perspective of practitioners working for the common good, and particularly of those working for Caritas, rather than an academic appreciation of all the different contested understandings of the common good.